(untitled) (Progress Annals: Journal of Progressive Research, 2024)
The article "Features of the development of small business and private entrepreneurship in the regions of the Republic of Uzbekistan" explores important aspects of the development of small business. The historical stages of development, peculiarities and challenges faced by small enterprises in various parts of the country are discussed. The impact of the state support policy on small businesses is analysed and examples of successful practices from various regions are given. In conclusion, conclusions are drawn about the importance of small business for the economic development of Uzbekistan and recommendations are offered to improve the situation of small enterprises in the regions of the country.